Potential Distribution of Six North American Higher-Attine Fungus-Farming Ant (Hymenoptera: Formicidae) Species. Issue 6 (19th December 2019) - Senula, Sarah F; Scavetta, Joseph T; Banta, Joshua A; Mueller, Ulrich G; Seal, Jon N; Kellner, Katrin
Abstract: Ants are among the most successful insects in Earth's evolutionary history. However, there is a lack of knowledge regarding range-limiting factors that may influence their distribution. The goal of this study was to describe the environmental factors (climate and soil types) that likely impact the ranges of five out of the eight most abundant Trachymyrmex species and the most abundant Mycetomoellerius species in the United States. Important environmental factors may allow us to better understand each species' evolutionary history. We generated habitat suitability maps using MaxEnt for each species and identified associated most important environmental variables. We quantified niche overlap between species and evaluated possible congruence in species distribution. In all but one model, climate variables were more important than soil variables. The distribution of M. turrifex (Wheeler, W.M., 1903) was predicted by temperature, specifically annual mean temperature (BIO1), T. arizonensis (Wheeler, W.M., 1907), T. carinatus, and T. smithi Buren, 1944 were predicted by precipitation seasonality (BIO15), T. septentrionalis (McCook, 1881) were predicted by precipitation of coldest quarter (BIO19), and T. desertorum (Wheeler, W.M., 1911) was predicted by annual flood frequency. Out of 15 possible pair-wise comparisons between each species' distributions, only one was statistically indistinguishable ( T. desertorum vs T. septentrionalis ). All other species distribution comparisons show significant differences between species. These models support the hypothesis that climate is a limiting factor in each species distribution and that these species have adapted to temperatures and water availability differently.